2019
DOI: 10.20524/aog.2019.0348
|View full text |Cite
|
Sign up to set email alerts
|

Children with diseases of the upper gastrointestinal tract are more likely to develop feeding problems

Abstract: Feeding problems may give rise to a number of adverse effects with organic, psychological, developmental and social impact. Specific medical conditions, especially diseases of the gastrointestinal system, are known to be associated with feeding problems. We searched databases, including MEDLINE and the Cochrane Library, for papers published in English from 1990 to March 2018. Keywords included “gastrointestinal diseases”, “gastroesophageal reflux disease”, “eosinophilic esophagitis”, “food allergy”, “children”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Feeding problems in young children are common, affecting almost one third of typically developing children and up to 80% of children with developmental disabilities [ 1 , 2 ]. Numerous studies have shown that children with gastrointestinal diseases, especially children with gastroesophageal reflux and eosinophilic esophagitis, face higher risk of developing feeding problems [ 3 ]. Feeding problems may have several organic, developmental, psychological, and sociological implications.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding problems in young children are common, affecting almost one third of typically developing children and up to 80% of children with developmental disabilities [ 1 , 2 ]. Numerous studies have shown that children with gastrointestinal diseases, especially children with gastroesophageal reflux and eosinophilic esophagitis, face higher risk of developing feeding problems [ 3 ]. Feeding problems may have several organic, developmental, psychological, and sociological implications.…”
Section: Introductionmentioning
confidence: 99%
“…Parental feeding practices significantly influence child eating behavior [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] . The data presented was obtained through a cross-sectional case control study that aimed to record parental practices to manage feeding problems in children with typical development and children with gastrointestinal diseases.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…For a long time, it has been known that medical disorders (i.e., prematurity, developmental disabilities) with associated gastrointestinal symptoms may lead to feeding problems in early childhood [ 3 , 4 , 5 , 6 ]. A growing body of literature has documented that gastrointestinal diseases such as gastroesophageal reflux, eosinophilic esophagitis or food gastrointestinal allergies are the primary organic causes of feeding problems in children with typical development [ 7 , 8 , 9 , 10 , 11 ]. The clinical manifestations of vomiting, constipation, abdominal pain and rectal bleeding and the repeated negative experiences with feeding have been associated with maladaptive feeding behaviors in these pediatric populations [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has documented that gastrointestinal diseases such as gastroesophageal reflux, eosinophilic esophagitis or food gastrointestinal allergies are the primary organic causes of feeding problems in children with typical development [ 7 , 8 , 9 , 10 , 11 ]. The clinical manifestations of vomiting, constipation, abdominal pain and rectal bleeding and the repeated negative experiences with feeding have been associated with maladaptive feeding behaviors in these pediatric populations [ 7 , 11 ]. Treatment models for childhood feeding problems consecrate on the mealtime environment and the caregivers’ feeding strategies [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%